Assessment of Visual Function in Patients with Myopic Foveoschisis. (2nd January 2019) - Li, Qingchen; Wang, Hao; Gao, Peng
ABSTRACT: Purpose: To assess the visual function in patient with myopic foveoschisis (MF). Methods: Fifty-one eyes of 51 subjects were enrolled and divided into myopic foveoschisis group (MFG, N  = 16), myopic control group (MCG, N  = 18), and normal control group (NCG, N  = 17) according to their diagnoses. Measurements of the logarithm of the minimum angle of resolution (LogMAR), the objective scatter index (OSI), the cut-off value of modulation transfer function (COMTF), the Strehl ratio (SR), the foveal threshold (FT), and the amplitude density (AD) in the first central ring of multifocal electroretinography were recorded and compared amongst groups. Results: LogMAR of MFG was the highest (MFG vs. MCG p ＜0.001, MFG vs. NCG p ＜0.001), and LogMAR of MCG and NCG were similar ( p  = 0.258). OSI of MFG was higher than that of MCG ( p ＜0.001), and the latter was higher than OSI of NCG ( p ＜0.001). COMTF was lowest in MFG, intermediate in MCG and highest in NCG (MFG vs. MCG p  = 0.001, MFG vs. NCG p ＜0.001, MCG vs. NCG p ＜0.001). SR, FT, and AD were all similar between MFG and MCG ( p  = 0.187, p  = 0.401, and p  = 0.446, respectively) while highest in NCG (SR MFG vs. NCG p ＜0.001, MCG vs. NCG p ＜0.001; FT MFG vs. NCG p  = 0.003, MCG vs. NCG p  = 0.025; AD MFG vs. NCG p ＜0.001, MCG vs. NCG p ＜0.001). Conclusions: Similarities were found between various functional parameters from different devices, revealing that the visual function in MF patients was impaired.